Role of CD26/dipeptidyl peptidase IV in human immunodeficiency virus type 1 infection and apoptosis. - Morimoto, C (1994)
To examine the role of CD26/dipeptidyl peptidase IV (DPPIV; EC 3.4.14.5) in infection by human immunodeficiency virus type 1 (HIV-1), we utilized CD26 cDNA-transfected Jurkat T-cell lines. Both CD26- parental Jurkat cells and mutant CD26+ (DPPIV-) transfected Jurkat cells were readily infected with HIV-1, whereas wild-type CD26+ (DPPIV+) transfected Jurkat cells were more resistant to HIV-1 infection. Our results suggest that CD26 is not essential for HIV-1 infectivity as suggested by others but that DPPIV enzyme activity may decrease the efficiency of HIV-1 infection. Of great interest, we found that mutant CD26+ (DPPIV-) transfectants and CD26- parental Jurkat cells strongly expressed CD95 (Fas/Apo-1) and were more sensitive than wild-type CD26+ (DPPIV+) transfectants to the induction of apoptosis by anti-CD95 monoclonal antibody. These results suggest that CD26 may play a role in HIV-1-associated loss of -CD4+ cells through the process of programmed cell death.